A linearly-tunable OTA-C sinusoidal oscillator for low-voltage applications - De Lima, Jader A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2002)
A low-voltage, low-power OTA-C sinusoidal oscillator based on a triode-MOSFET transconductor is here discussed. The classical quadrature model is employed and the transconductor inherent nonlinear characteristic with input voltage is used as the amplitude-stabilization element. An external bias VTUNE linearly adjusts the oscillation frequency. According to a standard 0.8μm CMOS n-well process, a prototype was integrated, with an effective area of 0.28mm2. Experimental data validate the theoretical analysis. For a single 1.8V-supply and 100mV≤VTUNE≤250mV, the oscillation frequency fo ranges from 0.50MHz to 1.125MHz, with a nearly constant gain KVCO=4.16KHz/mV. Maximum output amplitude is 374mVpp @1.12MHz. THD is -41dB @321mVpp. Maximum average consumption is 355μW.
Keywords: CMOS integrated circuits; Computer simulation; Electric network topology; Integrated circuit layout; MOSFET devices; Numerical analysis; Quadrature amplitude modulation; Transconductance; Transfer functions; Amplitude stabilization element; Circuit complexity; Finite source resistance; Maximum output amplitude; Oscillation frequency; Variable frequency oscillators